2003
DOI: 10.1042/bj20030438
|View full text |Cite
|
Sign up to set email alerts
|

S3 to S3' subsite specificity of recombinant human cathepsin K and development of selective internally quenched fluorescent substrates

Abstract: We have systematically examined the S3 to S3' subsite substrate specificity requirements of cathepsin K using internally quenched fluorescent peptides derived from the lead sequence Abz-KLRFSKQ-EDDnp [where Abz is o -aminobenzoic acid and EDDnp is N -(2,4-dinitrophenyl)ethylenediamine]. We assayed six series of peptides, in which each position except Gln was substituted with various natural amino acids. The results indicated that the S3-S1 subsite requirements are more restricted than those of S1'-S3'. Catheps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…3C), consistent with literature reports (68,69). We observed a minor preference for P 2 Lys (for the P 1 ϭ Arg sublibrary), consistent with a previous report of cathepsin K accepting P 2 basic residues (69).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…3C), consistent with literature reports (68,69). We observed a minor preference for P 2 Lys (for the P 1 ϭ Arg sublibrary), consistent with a previous report of cathepsin K accepting P 2 basic residues (69).…”
Section: Resultssupporting
confidence: 93%
“…Unlike the homologous cathepsins V, L, and H, cathepsin K also accepted Pro at the P 2 position. This P 2 Pro acceptance is required for the unique collagenase activity of cathepsin K (68) and has been noted previously in both PS-SCL (68) and fluorescence resonance energy transfer (FRET) studies (69). While cooperative interactions between substrate subsites cannot be detected using PS-SCLs, the study by Alves et al using FRET substrates had noted that the acceptance of P 2 Pro residues was dependent on the neighboring substrate residues.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Substrate specificity studies have shown that the primary specificity of papain-like cysteine proteinases is determined by S2-P2 interactions with a preference in cathepsin K for Pro or hydrophobic amino acids with aliphatic side chains (Leu, Ile, and Val) in the P2 position, whereas cathepsin L prefers bulky aromatic amino acids (Phe, Trp, and Tyr) or hydrophobic amino acids (67,68). In the P1 position, the substrate preference is similar in cathepsin L and K with a preference for amino acids with a hydrophilic side chain such as Arg, Lys, Gln, or Met (31,67,68), although amino acids with short side chains such as Gly or Ser can also be allowed (69,70 Both cathepsin K and L are expressed in osteoclasts (71), although cathepsin K is more abundant than cathepsin L at the mRNA (72,73) and activity (52) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides up to 20 residues can provide significant increases in florescence (de Souza et al 2000), allowing the measurement of the enzymatic activity on continuous base. The FRET peptides introduced by Chagas et al (1991) was a breakthrough in the study of proteases' specificity, and the synthesis of different Abzpeptidyl-EDDnp sequences provided the opportunity for us to study the activity of various endopeptidases such as human renin (Oliveira et al 1992), kallikreins (Chagas et al 1995, Del Nery et al 1995, Portaro et al 1997, Angelo et al 2006), cathepsin G (Réhault et al 1999, Korkmaz et al 2008), cathepsin D (Pimenta et al 2000, pro hormone convertase (Johanning et al 1998), lysosomal cathepsins (Portaro et al 2000, Alves et al 2003, Puzer et al 2004) and neprilysin (Medeiros et al 1997).…”
Section: Introductionmentioning
confidence: 99%